Integrated Water Management Digital Transformation Within Lower Yenisei River In Ice Season - Valery L. MIKHEEV; Valery M. ABRAMOV; Mikhail B. SHILIN; Evgeniy A. BAIKOV; Eugene P. ISTOMIN; Vyacheslav G. BURLOV; Vladimir N. ZAVGORODNIY; Oksana PETRIEVA; Yaroslav A. PETROV; Elena S. NOVOZHILOVA (Communications of International Proceedings, 2021)
Considered digital transformation results for integrated water management within lower Yenisei river in ice season under climate change and COVID-19 pandemic. The study uses situational analysis, risk management approach, web technologies and methods of building databases in distributed networks. As research result, it is recommended to use modelling and remote sensing data. As important research result, it was proposed to use developed digital decision aid instrument that combines heterogeneous resources in distributed networks. Demonstrated examples for last years. The presented research results have significant scientific novelty and can be useful for different players in integrated water management within lower Yenisei river in ice season. Platform https://www.researchgate.net/profile/Valery_Abramov2/ was used for data exchange and preliminary discussion during research.
Keywords: Natural Risks Management; Arctic Marine Fishery; Decision Support; Climate Change.